2012
DOI: 10.1126/scitranslmed.3003921
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant MG53 Protein Modulates Therapeutic Cell Membrane Repair in Treatment of Muscular Dystrophy

Abstract: Recombinant human MG53 protein can increase membrane repair after injury in cells and can reduce pathology in animal models of muscle injury and muscular dystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
340
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(366 citation statements)
references
References 53 publications
23
340
3
Order By: Relevance
“…3a, right panel, in response to injury caused by penetration of a microelectrode into the plasma membrane, GFP-MG53 rapidly translocated toward the acute injury site. This GFP-MG53 translocation to membrane injury sites in keratinocytes is similar to that observed in C2C12, HEK293, and other cell types (14,18).…”
Section: Defective Skin Structure In Mg53supporting
confidence: 80%
See 3 more Smart Citations
“…3a, right panel, in response to injury caused by penetration of a microelectrode into the plasma membrane, GFP-MG53 rapidly translocated toward the acute injury site. This GFP-MG53 translocation to membrane injury sites in keratinocytes is similar to that observed in C2C12, HEK293, and other cell types (14,18).…”
Section: Defective Skin Structure In Mg53supporting
confidence: 80%
“…rhMG53 protein was purified from Escherichia coli fermentation as described previously (18). rhMG53 was stored as lyophilized powder and dissolved in saline solution or encapsulated in hydrogel before use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor plasma membrane repair (PMR) is also associated with NiemannPick type A, 7 diabetes, 8 and ChediakHigashi 9 syndrome and therapies targeting PMR have been shown to be effective in treating muscle and lung injuries. [10][11][12] While much of the focus has been on disease resulting from poor PMR, we have recently identified that improved PMR is an important contributor for cancer metastasis. 13 Human breast cancer cells that turn metastatic through Keywords: actin, annexins, Annexin A2, breast cancer, cancer, plasma membrane repair, S100 proteins, S100A11, Metastasis up-regulation of truncated EGF receptor (ErbB2) also need to up-regulate their PMR machinery, and absence of enhanced PMR compromises their invasive ability.…”
Section: Introductionmentioning
confidence: 99%